Exploring the role of the atherogenic index of plasma as a mediator between body roundness Index and cardiovascular events in older adults: a NHANES-based study - Li, Kangming; Chen, Shizhong; Hu, Yanan; Qi, Chunmei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe rising incidence of cardiovascular diseases (CVD) in the elderly highlights the need for effective preventive strategies. Recent studies suggest that obesity, through metabolic factors, contributes to the development of CVD. This study aims to explore how body roundness index (BRI) levels affect the occurrence of CVD using data from the National Health and Nutrition Examination Survey (NHANES) (2003–2016), to better understand the role of obesity in CVD prevention and management.MethodsThe study analyzed data from 3,584 NHANES participants over seven cycles (2003–2016), dividing them into three groups (T1, T2, T3) based on BRI values. Univariate and multivariate regression analyses were used to assess the association between BRI and atherogenic index of plasma (AIP) levels with the occurrence of CVD. The mediating effect of AIP on BRI and CVD was also analyzed.ResultsCompared to the lowest tertile of BRI, participants with higher BRI levels had a higher proportion of females, smokers, drinkers, and individuals with lower educational attainment. Poverty-income ratio (PIR) and AIP levels were significantly higher, and the prevalence of CVD was also higher. BRI and AIP were both independent risk factors for CVD, with AIP having a significant mediating effect between BRI and CVD.ConclusionBRI levels significantly impact the occurrence of CVD through AIP mediation.